Clinical Spectrum of PRKAG2 Syndrome. (January 2016) - Porto, Andrea Giuseppe; Brun, Francesca; Severini, Giovanni Maria; Losurdo, Pasquale; Fabris, Enrico; Taylor, Matthew R.G.; Mestroni, Luisa; Sinagra, Gianfranco
Abstract : Supplemental Digital Content is available in the text.